Assessment of psychological support in patients with unilateral peripheral hypofunction - Laura Lijić; Tihana Mendeš; Andrijana Včeva; Željko Zubčić; Hrvoje Mihalj; Matej Rezo; Kristina Kralik; Hrvoje Vidić; Tamara Kopf; Antoneta Gudelj; Andrea Russo; Joško Šoda; et al. (Scientific Reports)
Abstract Nowadays, vestibular diseases are quite common in the population and significantly impair quality of life. Additionally, a notable problem is that a certain number of patients experience psychological consequences. Therefore, it is important to investigate the connection between vestibular damage and the potential need for psychological intervention. This study aims to examine the correlation between anxiety in individuals with unilateral peripheral vestibular disorder in relation to gender, age, and the existence of acute and chronic, compensated and uncompensated, partial and complete unilateral peripheral vestibular disorder. Additionally, it was important to determine the degree of free-floating anxiety, phobia-related anxiety, obsessiveness, somatic manifestations, depression, and hysteria in these patients using the Crown-Crisp Experience Index questionnaire. The study included 54 patients, 39 (72%) female and 15 (28%) male, with an average age of 61.5 ± 13.5 years. Results showed that the majority of participants had pronounced somatic anxiety (29.6%), followed by depression (14.8%), free-floating anxiety (9.4%), phobia-related anxiety (7.4%) and hysteria (7.4%) equally represented, and obsessiveness (1.8%) being the least pronounced. Nearly all participants (94%) were diagnosed with chronic hypofunction due to presenting for examination and diagnostic processing after the acute phase of the disease had ended. To conclude, no significant differences were observed in the common symptoms or personality traits within conventional categories of psychoneurotic and neurotic symptomatology concerning gender or the presence of vestibular hypofunction.